Konsep Desain Objek Wisata Kuliner Seafood di Kabupaten Jembrana, Bali - Made Yogi Wikrama Putra; I Kadek Merta Wijaya; I Wayan Widanan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
At present, the kinds of foods have begun to develop with different kinds of input from children to parents wanting to try a wide variety of growing foods, with restaurants that feed only 1 types of raw materials and yet can produce a variety of items that the buyer can select at his or her own convenience. The jembrana county has a high capacity of fisheries, but it is not comparable to the tourists visiting the jembrana district, with a demand to use the fisheries sector to attract tourists to the jembrana district with planning and designing a seafood tourist attraction in the jembrana district, Bali. The survey methods used are those with associated agencies that survey to get the data used. A literacy study method, which is a data study method done by retrieving needed data from the corresponding literature. As well as a method of field observation: direct observation to location. The concept of touring seafood is going to be an attraction in this building. Green architectural themes are expected to enable visitors to visit the seafood culinary attractions that capture the seafood culinary atmosphere by savoring the natural and ecologically sound of buildings in operation